PRODUCTION OF CARBON DISULFIDE BY CHARCOAL-SULFUR PROCESS - zainab Amer Mohammed; Amal Ali Sanun; Ruqaia AbuAjila Sheliq (Surman Journal of Science and Technology, 2025)
Historical background of the production of Carbon Disulphide (CS2) has been presented. Chemistry and physical properties of (CS2) as well as its end uses and world producers have been also presented. All manufacturing processes for carbon disulphide have been discussed and compared. The main objective behind this project is to describe, in detail, the process of (CS2) production based on the reaction of Charcoal with Sulphur, that is the Retort Process. For this process, detailed theoretical and practical calculations have been done. Moreover, sample design calculations for some important equipments have been accomplished. These quipments are sulphur melting tank together with the agitator and molten sulphur pump, and condenser for Carbon Disulphidemic calculations performed in this work show that the manufacturing cost of (CS2) is (3139 ) per ton. The economic study also shows that Breakeven point (QBE) and Payback- Period of the plant are (7.5t/day) and (5.3) years respectively. It is suggested in this work that a Retort Process Plant of moderate capacity can be constructed in Libya to meet the demand for (CS2) by different consumers. The site preferred for the plant is that nearer to the big consumers of (CS2) as well as that in districts where raw materials,mainly sulphur, are available.